Analisis Keseimbangan Jumlah Armada Angkutan Umum Berdasarkan Kebutuhan Penumpang - Putra, Adris A. (MEDIA KOMUNIKASI TEKNIK SIPIL, 2013)
Urban area developing marked by there is in height of people activities/mobility in the effort to meet their need. The direct implication from the condition trigger to arise main problem, which is in term of transportation means supply. Increasing of transportation service demand is supporting people activities of Makassar City, therefore public transportation from time to time continually increase without the limitation of fleet amount that operating, so causing total fleet are incommensurate to people recruitments, and condition of public transport service by following activity broadcast pattern and city area using with radial causes several road internodes are passed of city transport route will overlap on one another because total operating fleet are incommensurate to passenger requirement (over supply). From the analysis result by using pick up and drop off data of public transport passengers (load factor) average only 0.33 percent on operating route in makassar city, that percentage show that publics transport fleet amount which necessarily be of service according to passenger requirement outgrow in Makassar City are 2.283 vehicle unit public or 51.5 % of 4.511 stock vehicle unit public transport.